2011
DOI: 10.1371/journal.pone.0019022
|View full text |Cite
|
Sign up to set email alerts
|

Soccer Attenuates the Asymmetry of Rectus Abdominis Muscle Observed in Non-Athletes

Abstract: PurposeTo determine the volume and degree of asymmetry of the rectus abdominis muscle (RA) in professional soccer players.MethodsThe volume of the RA was determined using magnetic resonance imaging (MRI) in 15 professional male soccer players and 6 non-active male control subjects.ResultsSoccer players had 26% greater RA volume than controls (P<0.05), due to hypertrophy of both the dominant (28% greater volume, P<0.05) and non-dominant (25% greater volume, P<0.01) sides, after adjusting for age, length of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 27 publications
5
20
0
Order By: Relevance
“…This was an additional proof to demonstrate the various rotational stuck of sacrum in Oblique and Antero-posterior axis. Which we were neglects to display in our previous work [5,6]. The present study also observed that, the instability of Multifidus and Erector spinae were results in results in Bilateral dysfunctions in Transverse axis dysfunctions.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…This was an additional proof to demonstrate the various rotational stuck of sacrum in Oblique and Antero-posterior axis. Which we were neglects to display in our previous work [5,6]. The present study also observed that, the instability of Multifidus and Erector spinae were results in results in Bilateral dysfunctions in Transverse axis dysfunctions.…”
Section: Discussionsupporting
confidence: 54%
“…The sacroiliac joint was formed by the articulation of sacrum and ilium to complete the bony pelvis. Numerous ligaments firmly strap the sacroiliac joints together to balance out the bony pelvis, and also it decreases the movement of the joint [5,6,15].…”
Section: Introductionmentioning
confidence: 99%
“…Between-limb comparisons are most commonly measured by assessing muscle strength and torque. Idoate et al 13 reported non-dominant side hypertrophy of the rectus abdominis in professional players, which they speculate was stronger to provide for the stabilizing demands of the non-kicking limb. In elite soccer players, Aginsky and Neophytu 14 reported greater hamstring strength and endurance in the dominant limb, agreeing with Blache and Monteil 15 who concluded that greater dominant limb knee flexor and extensor strength existed at 40% and 60% maximal load in a sample of recreational players.…”
Section: Introductionmentioning
confidence: 98%
“…On assessment we taught the subjects how to perform the movements to gain access to the malalignment of both Innominate bones of the bony pelvis unit. In addition, to justify our diagnosis we access the muscles of the functional slings and the muscles around the bony pelvis related to the malalignment of the pelvic unit (Abdolhamid Daneshjoo, 2013), (Julie Hides, 2012), (Fernando Idoate, 2011). We encouraged all the subjects to relax and told them that the movements would not be judged as "good" or "bad."…”
Section: Methodsmentioning
confidence: 99%